Influence of Molding Mixture Composition on TOC and BTEX Emissions - Šindlerová, E. (Archives of Foundry Engineering, 2026)
The work deals with the issue of BTEX (benzene, toluene, ethylbenzene, xylenes) and TOC (Total Organic Carbon) emissions arising from molding mixtures due to the decomposition of organic compounds at high temperatures and lack of oxygen. The measurements are focused on the combination of bentonite molding mixture with cold-box cores, which is very often used for casting cast iron castings, especially in serial and mass production. The number of emissions is controlled by changing the air access to the mold by choosing the grain size of the silica sand and optimizing the mold-metal ratio by changing the height of the molding mixture above the casting. The highest measured TOC value was in the mold made of mixture ŠH32/E/4CB/20, which exceeded the still valid limit of 150 mgC/m3. The TOC values of the other molds were around the limit of 50 mgC/m3. The amount of BTEX emissions correlates with TOC measurements, where up to 3 times more emissions were released from the molds prepared of ŠH32/E/4CB/20. The idea behind the measurements is find a simple and easily applicable methods for foundry industry leading to a reduction in TOC and BTEX emissions. The results so far show that by optimizing the composition of the molding mixture and adjusting the ratio between the molding mixture and the metal, the amount of these emissions can be effectively reduced. The influence of the type of used silica sand, especially its squareness, origin and the ability of different types of bentonites to absorb the resulting harmful compounds and thus reduce emissions released from the molds remains an open question.